A hybrid FEC-ARQ protocol for low-delay lossless sequential data streaming - Huang, Ying-zong; Mehrotra, Sanjeev; Li, Jin (2009 IEEE International Conference on Multimedia and Expo, 2009)
Interactive Internet Applications that rely on sequential streams for lossless data exchange often use retransmission protocols (e.g. TCP) for reliability and the guarantee of sequential data ordering. More so than for bulk file transfer or media delivery, lossless sequential streaming poses an even greater challenge for the common problem cases of retransmission protocols, such as lossy links or long network paths, manifesting as significant latency in the interactive user experience. We propose a hybrid FEC-ARQ protocol built on a packet streaming code that reduces to a simple strategy over sending or resending original data packets or check packets combining undecoded packets, based on actual network conditions. Experimental results show that our proposed protocol can significantly improve the total delay over retransmission and other schemes that use FEC, under a range of bandwidth and loss scenarios.